"More than words" – Longitudinal linguistic changes in the works of a writer diagnosed with semantic dementia. Issue 3 (4th May 2021) - Hwang, Yun Tae; Strikwerda-Brown, Cherie; El-Omar, Hashim; Ramanan, Siddharth; Hodges, John R; Burrell, James R; Piguet, Olivier; Irish, Muireann
ABSTRACT: Leveraging recent advances in automated language analysis and anovel statistical approach utilizing an independent control group, we explored changes in lexical output across two published works of a man diagnosed with semantic dementia. We found significant increase in adverb usage and decline in familiarity, meaningfulness, age of acquisition and co-occurrence probability over 2 years. Collectively, these indices suggest that WR's narrative structure became progressively simpler, lexically less sophisticated, and that words commonly associated together no longer appeared in close proximity. Our study illustrates how degeneration of the semantic knowledge base impacts the production, content, and quality of literary works.